THE RELATION BETWEEN HEALTH KNOWLEDGE AND “BSE” ATTITUDE AS AN EFFORT FOR EARLY DETECTION OF BREAST CANCER IN YOUNG WOMEN AT HIGH SCHOOL 1 KETAPANG, SOUTH LAMPUNG 2022 - Anggiyanti, Finisia; Santosa, Puji Raharja; Dinda Nur Fajri Hidayati Bunga (Rena Cipta Mandiri, 2024)
Breast cancer ranks first of all cancers that occur in women. Currently, most breast cancer sufferers are young, not even a few are 14 years old and in Indonesia more than 80% of cases are found to be in an advanced stage, where treatment is difficult to do this is due to low health knowledge about early detection of breast cancer. . Early detection of breast cancer can be done by doing BSE. The purpose of this study was to determine the relationship between health knowledge and the attitude of